2013
DOI: 10.1161/atvbaha.112.300329
|View full text |Cite
|
Sign up to set email alerts
|

Peptide Inhibitor of CXCL4–CCL5 Heterodimer Formation, MKEY, Inhibits Experimental Aortic Aneurysm Initiation and Progression

Abstract: Objective Macrophages are critical contributors in abdominal aortic aneurysm (AAA) disease. We examined the ability of MKEY, a peptide inhibitor of CXCL4-CCL5 interaction, to influence AAA progression in murine models. Methods and Results AAAs were created in 10-week-old male C57BL/6 mice by transient infrarenal aortic porcine pancreatic elastase (PPE) infusion. Mice were treated with MKEY via intravenous injection either 1) before PPE infusion, or 2) after aneurysm initiation. Immunostaining demonstrated CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(86 citation statements)
references
References 57 publications
0
86
0
Order By: Relevance
“…Still, we found a significantly lower expression of potent chemotactic mediator chemokine CCL2, which may reflect a negative feedback regulation of leukocyte infiltration in order to keep the inflammation at a very low level. This finding is very interesting since experimental studies have suggested beneficial effects of chemokine inhibition on formation of aneurysms [8], but future studies specifically targeting chemokines should clarify their contribution to this pathology. Another interesting aspect regarding production of reactive oxygen species has also been associated with human aortic aneurysms [10].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Still, we found a significantly lower expression of potent chemotactic mediator chemokine CCL2, which may reflect a negative feedback regulation of leukocyte infiltration in order to keep the inflammation at a very low level. This finding is very interesting since experimental studies have suggested beneficial effects of chemokine inhibition on formation of aneurysms [8], but future studies specifically targeting chemokines should clarify their contribution to this pathology. Another interesting aspect regarding production of reactive oxygen species has also been associated with human aortic aneurysms [10].…”
Section: Discussionmentioning
confidence: 79%
“…A combination of causes is assumed in patients with bicuspid aortic valve, which have a higher risk of aortic dilation or dissection, probably due to altered regional hemodynamics and structural anatomy of the aortic wall [5,6]. Inflammation has also been suggested in the development of abdominal aortic aneurysms, since cellular infiltration via vasa vasorum was observed in the aortic wall and associated with expression of inflammatory mediators [7,8]. Because of differences in aetiologies [9], these findings from abdominal aneurysms cannot be directly projected into thoracic aneurysms, where we lack an evidence for inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Additional inflammatory pathways are also involved in the action of Ang II. Some evidence has suggested that CCL5 also has an important role in Ang II induced dissecting AAA [41]. Moreover, Ang II may stimulate the expression of cyclooxygenase-2 (COX-2) [42,43], a critical enzyme in AAA pathogenesis that forms vasoactive and inflammatory prostaglandins.…”
Section: Renin Angiotensin System -Classical Systemmentioning
confidence: 99%
“…Moreover, the heteromeric form of CXCL4 may also bind to receptors other than CXCR3, for the activation of T-cells. Blocking these heteromerization may require further studies and can be a valuable therapeutic target as it has been shown in the case of aortic aneurysm [26].…”
Section: Platelet -Specific Cytokines and Cerebral Malariamentioning
confidence: 99%